Horizontal Vestibulo-Ocular Reflex Gain Measures During Convergence Using a Monocular Video Technique - Figtree, William V C; Schubert, Michael C; Migliaccio, Americo A (Otology & neurotology, 2020)
Vestibulo-ocular reflex (VOR) response measures during convergence, which are clinically important to measure peripheral vestibular organ function during rotational and translational rapid head movements, can be implemented using existing clinically available monocular video-oculography (VOG) systems. We have developed and validated a monocular VOG technique that allows for accurate measurement of the convergence angle immediately before a rapid translational or rotational head movement. We recorded binocular eye movements while subjects performed active or passive horizontal head impulses while viewing near and far targets. We calculated the convergence angles and VOR gains using monocular and binocular methods and compared them with a geometric model. The monocular VOG technique resulted in convergence angle and VOR gain (eye velocity/head velocity) calculations that differed by ∼10% compared with values calculated using the binocular data. The monocular VOG technique can be clinically implemented using any unmodified, commercially available, monocular VOG system, provided its camera can be positioned to track either eye. Many vestibular clinics already have access to such systems. This method makes possible reliable measurement of the near-viewing horizontal angular VOR during the head impulse test, the translational VOR during the head heave test in patients, and the clinical measurement of convergence insufficiency.